Oxidative stress-induced cyclin D1 depletion and its role in cell cycle processing - Pyo, Chul-Woong; Choi, Joon Hwan; Oh, Sang-Muk; Choi, Sang-Yun (Biochimica et biophysica acta, 2013)
Cyclin D1 is immediately down-regulated in response to reactive oxygen species (ROS) and implicated in the induction of cell cycle arrest in G2 phase by an unknown mechanism. Either treatment with a protease inhibitor alone or expression of protease-resistant cyclin D1 T286A resulted in only a partial relief from the ROS-induced cell cycle arrest, indicating the presence of an additional control mechanism. Cells were exposed to hydrogen peroxide (H2O2), and analyzed to assess the changes in cyclin D1 level and its effects on cell cycle processing by kinase assay, de novo synthesis, gene silencing, and polysomal analysis, etc. Exposure of cells to excessive H2O2 induced ubiquitin-dependent proteasomal degradation of cyclin D1, which was subsequently followed by translational repression. This dual control mechanism was found to contribute to the induction of cell cycle arrest in G2 phase under oxidative stress. Silencing of an eIF2α kinase PERK significantly retarded cyclin D1 depletion, and contributed largely to rescuing cells from G2 arrest. Also the cyclin D1 level was found to be correlated with Chk1 activity. In addition to an immediate removal of the pre-existing cyclin D1 under oxidative stress, the following translational repression appear to be required for ensuring full depletion of cyclin D1 and cell cycle arrest. Oxidative stress-induced cyclin D1 depletion is linked to the regulation of G2/M transit via the Chk1–Cdc2 DNA damage checkpoint pathway. The control of cyclin D1 is a gate keeping program to protect cells from severe oxidative damages. •Cyclin D1 depletion is implicated in ROS-induced cell cycle arrest.•Exposure of cells to ROS immediately induced proteolysis of cyclin D1.•Exposure to excessive ROS activated Perk-mediated translation repression.•Cyclin D1 is linked to the regulation of G2/M transit via the Chk1 pathway.